Practice patterns of prenatal and perinatal testing in Canadian cytogenetics laboratories. (25th April 2021) - Ashfield, Tamara; McCready, Elizabeth; Shago, Mary; Wang, Hong; Sinclair‐Bourque, Elizabeth; Cappa, Eva; Piche Marolt, Amanda; Chun, Kathy
Abstract: Objective: To survey patterns of practice in Canadian cytogenetics laboratories and evaluate whether newer technologies have influenced testing algorithms for the detection of common aneuploidies and other genomic imbalances in the prenatal and perinatal settings. Methods: Cytogenetics laboratories across Canada were invited to participate in two patterns‐of‐practice surveys: one in 2016 and one in 2019. They were asked to identify the prenatal and perinatal specimen types tested at their facility and which testing methods were used for initial testing and for follow‐up. Results: All clinical laboratories performing prenatal testing offer rapid aneuploidy detection (RAD). Most laboratories also offer microarray analysis. A positive result is either followed up by karyotyping or no further testing is performed. For prenatal samples, a negative result may be followed up by microarray or karyotyping and is dependent on the reason for referral. For perinatal samples, availability of microarray to follow up a negative result is increasing. Conclusions: Since 2016, the availability of RAD as a first‐line test in Canadian cytogenetics laboratories remains consistent, while microarray has become the preferred follow‐up testing method over traditional karyotyping following a normal RAD result. Despite a universal healthcare system, disparities in prenatal and perinatal cytogenetic testing algorithms are apparent. Key points: What's already known about this topic? Chromosome abnormalities are recognized as a common cause of miscarriage and congenital anomalies Until recently, karyotype assessment of G‐banded metaphases has been the gold standard for detection of chromosome abnormalities in the prenatal and perinatal period Development of molecular cytogenetic tools has allowed for direct testing of tissues, reduced turnaround times and increased sensitivity for small, potentially clinically significant copy number changes What does this study add? This study provides an overview of the available technologies in Canadian clinical cytogenetics laboratories and their use in the prenatal and perinatal settings Despite a universal healthcare system, a uniform common practice is not apparent, although there is a distinct trend towards microarray and away from karyotyping and FISH after a normal rapid aneuploidy detection result These survey results highlight emerging trends in Canadian clinical cytogenetics laboratories and provide information for laboratories to advocate for additional resources if local practices are not aligned with these trends